Potensi Kain Shibori sebagai Strategi Penguatan Ketahanan Ekonomi dalam Menghadapi Masa Pandemi - Fuad Hasyim (UIN Raden Mas Said Surakarta, 2021)
This community service aims to increase the motivation of young people to have an entrepreneurial spirit in the midst of a pandemic. Community service activities consist of trauma healing and entrepreneurship training. Entrepreneurship training in the form of making cloth and shibori t-shirts. During the pandemic, the rate of psychological disorders reached 64.8%. Some of the effects of these disorders are anxiety (65%), depression (62%) and trauma (75%). Therefore, trauma healing is expected to reduce anxiety, depression and trauma. Then continued with entrepreneurship training to restart, motivate creativity and increase optimism among young people with activities that have economic value to survive during the pandemic. The selection of shibori fabrics and shirts is due to the ease of obtaining raw materials, affordability of prices and good business prospects. The subjects of the service are Ikatan Pelajar Nahdlatul Ulama (IPNU) and Ikatan Pelajar Putri Nahdlatul Ulama (IPPNU) Pimpinan Cabang Boyolali as representatives of youth in the Boyolali Regency area. The service was held at the Kemasan Village Hall, Sawit, Boyolali. The results show that community service activities are able to reduce the level of psychological disorders and are able to increase the motivation of young people to become entrepreneurs. The indicators are attitude (sig. 0.005), subjective norm (sig. 0.000) and perceived behavioral control (0.047) have a significant effect on interest in entrepreneurship. The hope is that after carrying out community service and providing assistance for the shibori cloth and shirt business, it will be able to improve the family economy and in aggregate be able to create economic resilience during the pandemic.